Trends, impacts, and emerging perspectives on divorce in Kerala- a review approach - Anas Tharakan (Discover Global Society, 2025)
Abstract This study aims to comprehensively understand the phenomenon of divorce in the context of Kerala, with a focus on its psychosocial and economic dimensions, as well as its diverse effects and impacts, through a systematic review approach. In India, the divorce rate is very low. However, Kerala has the most significant number of divorces. According to data from family courts, around 75 divorces occur in Kerala every single day. In this context, it becomes increasingly important to compile and study various research works on divorces in Kerala to gain a deeper understanding of the situation. The study used the systematic review approach based on an in-depth analysis of 13 research studies conducted between 2010 and 2024, all focusing on Divorce and its multifaceted impacts within the context of Kerala. The study synthesizes findings on demographic dimensions, reasons for Divorce, and its impacts, including psychosocial and economic effects, as well as its impact on children. The study also analyses divorce trends in religious and legal aspects, highlighting that employment is the most influential demographic factor contributing to Divorce. Kerala's rising divorce rate calls for balanced, inclusive research addressing gaps like remarriage, legal awareness, and male perspectives while exploring both negative and positive outcomes. Studies should focus on longitudinal and solution-oriented approaches to better understand and mitigate divorce-related challenges. Comprehensive research will inform effective policies and interventions for addressing divorce complexities in Kerala.